The Factors Causing Changes in Community Livelihoods Around the Industrial Area in Sirnabaya Village, East of Telukjambe District, Karawang Regency, West Java Province - Juliati Prihatini; Siti Zulaika (AIBPM Publisher, 2021)
Sirnabaya Village in East of Telukjambe District has less productive land, yet it has strategic location for industrial area, that the land was sold to business owners causing the local people change their livelihoods from agricultural sector to industrial sector. The presence of the industry around the village is not automatically able to hire a large number of workers from local people, due to the fact that the required skills do not meet the requirement. This study aims to find out the factors causing changes in community livelihoods. The method used in this study was descriptive qualitative. The data collection techniques conducted through interviews and documentation. The result showed that the presence of industry has a multiplier effect on local people, yet the effect brings benefit to the government.